2013
DOI: 10.4236/ojn.2013.32023
|View full text |Cite
|
Sign up to set email alerts
|

The effects of incivility on nursing education

Abstract: Incivility in the population has become of great interest within the past decade, particularly in the wake of the school massacre in Columbine and the recent movie theatre mass murder in Aurora, Colorado. While citizens struggle to make sense of these violent behaviors, higher education officials are perhaps most vested in exploring the causes, displays, and solutions to uncivil behavior among both faculty and students. The effects of incivility, whether classified as minor disruptions or major violence, may a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…Introverted students, and likely those who are shy and/or highly sensitive, respond more positively to gentle, as opposed to aggressive, mannerisms and language. Schaeffer [56] found that students who were exposed to intimidation over time from faculty in a nursing program tended to suffer actual psychological and physiological symptoms, including anxiety, depression, gastro-intestinal disease, and mood disorders.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Introverted students, and likely those who are shy and/or highly sensitive, respond more positively to gentle, as opposed to aggressive, mannerisms and language. Schaeffer [56] found that students who were exposed to intimidation over time from faculty in a nursing program tended to suffer actual psychological and physiological symptoms, including anxiety, depression, gastro-intestinal disease, and mood disorders.…”
Section: )mentioning
confidence: 99%
“…Educators who customize requirements within the framework of their courses are demonstrating their respect for students as individuals. An added benefit of allowing students to make decisions about how they will learn, and the standards of performance toward which they will strive, is that students will experience, and learn from, the results of their choices [56]. Faculty also benefit because they can observe students in the process of analyzing course materials and tackling problems, and can then use their expertise to intercede as necessary-a creative and fulfilling aspect of the teaching role [3].…”
Section: Making Decisions About In-class Presentationsmentioning
confidence: 99%
“…Very few studies regarding the online nursing education environment have been reported, however, other authors have documented the occurrence of incivility in traditional learning environments. [2] Shaeffer [3] noted that consequences of incivility for nursing include the potential for academic incivility to "contribute to bullying in the workplace. .…”
Section: Introductionmentioning
confidence: 99%
“…Students can feel defenseless, anxious, dehumanized, and angry in response. 13 In addition, nursing students who lack a positive connection with their teachers or mentors need more guidance and worry about making mistakes. 4 They also have difficulty distinguishing appropriate from inappropriate behaviors.…”
Section: Early Exposurementioning
confidence: 99%